Potensi dan Peluang Implementasi Ik-Cepa terhadap Perluasan Akses Pasar Perdagangan Barang dan Jasa Indonesia Dipasar Korea Selatan - Anto Purwanto (Jurnal Syntax Admiration, 2024)
The Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA) is a bilateral free trade agreement (FTA) between Indonesia and South Korea which covers the areas of trade in goods, services, investment, economic, legal and institutional cooperation. The aim of this research is to analyze the impact of IK-CEPA implementation on trade in goods and services between Indonesia and South Korea. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the implementation of IK-CEPA has influenced trade in goods and services between Indonesia and South Korea, which has led to increased trade, investment, technological progress and cooperation between the countries. However, there are still several obstacles that need to be overcome to maximize the benefits of IK-CEPA, including a lack of information about IK-CEPA among entrepreneurs and limited production capacity in Indonesia.